THE USE OF GADGETS WITH THE PSYCHOSOCIAL DEVELOPMENT OF PRESCHOOL-AGE CHILDREN - Utami, Rahayu Budi; Ula, Silvia Nadiyatul; Suroso, Heri; Ekwantoro, Ekwantoro; Paraswati, Mareta Deka (SYNTHESIS Global Health Journal, 2023)
Background. Preschool-age children experience several developments, one of which is psychosocial development. Uncontrolled use of gadgets as a distraction so that children are not fussy or lonely will cause children not to learn to communicate and socialize naturally with the environment. This study aims to determine the relationship between gadget use and psychosocial development of preschool children in TK Pertiwi 1 Sambirejo, Tanjunganom District, Nganjuk Regency. Research Method. This study used an analytical survey design with a cross sectional study approach. The population are all mothers and children of preschool children was 48 mothers and children. Used Purposive Sampling technique. A sample of 46 respondents according to the inclusion and exclusion criteria. The independent variable was the use of gadget and the dependent variable was psychosocial development. Data collection used questionnaires, observations and interviews. Statistical test using Coefficient Contingency with a significant level of a < 0.05. Findings. From 46 respondents, most had a moderate category of gadget use as many as 24 respondents (52.2%) and most showed psychosocial development of guilt as many as 25 respondents (54.3%). The results of the statistical test obtained p value 0.002 < 0.05 with r = 0.469 which shows the closeness of the relationship so that Ha was accepted which means there was a relationship between the use of gadgets and psychosocial development of preschool children. Conclusion. The use of gadgets can affect the psychosocial development of preschool children. Good stimulation, optimal use of gadgets so that children's psychosocial development develops well.